2018
DOI: 10.1371/journal.pone.0195870
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical analysis of the corrosion inhibition effect of trypsin complex on the pitting corrosion of 420 martensitic stainless steel in 2M H2SO4 solution

Abstract: Inhibition effect of trypsin complex (TC) on the pitting corrosion of martensitic stainless steel (type 420) in 1M H2SO4 solution was studied with potentiodynamic polarization, open circuit potential measurement and optical microscopy. TC reduced the corrosion rate of the steel with maximum inhibition efficiency of 80.75%. Corrosion potential shifted anodically due to the electrochemical action of TC. The pitting potential increased from 1.088VAg/AgCl (3M) at 0% TC to 1.365VAg/AgCl(3M) at 4% TC. TC shifts the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The entire processes of uniform and localized corrosion are known to result from the usual electrochemical reactions such as charge transfer, dissolution of metal anodes into electrolytes, and mass transport phenomena during flow [5]. Studies performed on metastable and stable pit growth of metals and alloys have shown that the dissolution of metals via pitting corrosion tends to be stochastic rather than a visible catastrophic process, which makes the material failure more life-threatening than other corrosion damages [5][6][7]. In most cases, the corrosive damage is in its advanced stages before detection can be made.…”
Section: Introductionmentioning
confidence: 99%
“…The entire processes of uniform and localized corrosion are known to result from the usual electrochemical reactions such as charge transfer, dissolution of metal anodes into electrolytes, and mass transport phenomena during flow [5]. Studies performed on metastable and stable pit growth of metals and alloys have shown that the dissolution of metals via pitting corrosion tends to be stochastic rather than a visible catastrophic process, which makes the material failure more life-threatening than other corrosion damages [5][6][7]. In most cases, the corrosive damage is in its advanced stages before detection can be made.…”
Section: Introductionmentioning
confidence: 99%